PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia 2012-2013) - Novia Bani Nugraha; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
The aim of this study are to examine the effect of corporate social responsibility (CSR), size of firm, profitability, leverage and capital intensity to tax aggresiveness. The independent variables are used in this study are corporate sosial responsibility disclosure, size of firm, profitability, leverage and capital intensity. While the dependent in this study is tax aggresiveness tahe measured using two kind of effective tax rates (ETR).Population taken as the object of observation amounted 794 non-financial companies listed in Indonesia Stock Exchange in the 2012-2013 period. Determination of the sample was made by applying purposive sampling method and obtaining a sample of 240 manufacturing companies based on certain criteria.The result showed tat the CSR and leverage significant effect on the tax aggresiveness. While size, profitability and capital intensity does not significantly influence the tax aggresiveness.